PJMHS 2021
DOI: 10.53350/pjmhs2115113447
|View full text |Cite
|
Sign up to set email alerts
|

A Cross Sectional Study on the Rising Frequency of Gallbladder Stones

Abstract: Objective: The aim of this study was to determine the occurrence of cholelithiasis in the city of Lahore and its surrounding area. Material and Methods: This study was conducted at Shalamar Medical and dental college Lahore and data for this study was collected from different hospitals of Lahore and the duration of this study was from 2019 to 2021. The participants of this study were from both genders’ male and female from of the age of 10 years to 80 years, and the sample size for this study was 483 and 1583… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
(11 reference statements)
1
2
0
Order By: Relevance
“…It was observed that both physical and mental health was suboptimal in children residing in orphanages in the twin cities. Comparable results were reported in previous studies by Hassan et (3,18). The presence of low BMI among orphans, especially among younger age groups, has also been observed among the orphans of Southern Ethiopia as well as those living in Odisha, India, where around 27% and 32% of the orphans were found to be underweight respectively.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…It was observed that both physical and mental health was suboptimal in children residing in orphanages in the twin cities. Comparable results were reported in previous studies by Hassan et (3,18). The presence of low BMI among orphans, especially among younger age groups, has also been observed among the orphans of Southern Ethiopia as well as those living in Odisha, India, where around 27% and 32% of the orphans were found to be underweight respectively.…”
Section: Discussionsupporting
confidence: 65%
“…In terms of physical health, orphans in Pakistan may face challenges regarding malnutrition, lack of access to healthcare, and exposure to infectious diseases. Additionally, they may be more susceptible to physical abuse and neglect (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation